The Discourse of the Capital City of Nusantara: Learn from President’s Tweets - Sapto Setyo Nugroho; Yonarisman Muhammad Akbar (Yayasan Ilomata, 2023)
This paper examines the construction and contextuality of the discourse on the Capital City of the Nusantara by President Joko Widodo's Twitter account. Focusing on the phenomenon of the relocation of the capital city with a discourse perspective can contribute to discussions about the operation of ideological power in power through political or governmental communication. Using the research method of critical discourse analysis, this paper finds that the discourse on the new State Capital is constructed through three stages of discourse, namely the study discourse, the strategic decision discourse, and the political economy consolidation discourse. While the context in the discourse is in three situations, namely the agenda engineering situation, the policy formulation situation, and the policy implementation situation. These three situations have tug-of-war at their respective moments and tend to create contradictions between one statement and another from President Joko Widodo about the new National Capital. However, the context of the discourse on the new State Capital by President Joko Widodo in this paper also tends to prove the arguments in previous writings, namely that President Joko Widodo is building a legacy strategically in ambitious ways.